Gastrodin Improves Nonalcoholic Fatty Liver Disease Through Activation of the Adenosine Monophosphate–Activated Protein Kinase Signaling Pathway. Issue 6 (24th September 2021) - Wan, Juan; Zhang, Yanyan; Yang, Diqi; Liang, Yongjie; Yang, Ling; Hu, Sha; Liu, Zhen; Fang, Qian; Tian, Song; Ding, Yi
Abstract : Background and Aims: NASH is currently one of the most common causes of liver transplantation and hepatocellular carcinoma. Thus far, there is still no effective pharmacological therapy for this disease. Recently, Gastrodin has demonstrated hepatoprotective effects in a variety of liver diseases. The aim of this study is to investigate the function of Gastrodin in NASH. Approach and Results: In our study, Gastrodin showed potent therapeutic effects on NASH both in vivo and in vitro . In high‐fat diet or high‐fat and high‐cholesterol diet–fed mice, the liver weight, hepatic and serum triglyceride and cholesterol contents, and serum alanine aminotransferase and aspartate aminotransferase activity levels were markedly reduced by Gastrodin treatment as compared with the corresponding vehicle groups. Notably, Gastrodin showed minimal effects on the function and histological characteristics of other major organs in mice. We further examined the effects of Gastrodin on lipid accumulation in primary mouse hepatocytes and human hepatocyte cell line and observed that Gastrodin showed a significant decrease in lipid accumulation and inflammatory response in hepatocytes under metabolic stress. Furthermore, RNA‐sequencing analysis systemically indicated that Gastrodin suppressed the pathway and key regulators related to lipid accumulation, inflammation, and fibrosis in the pathogenesis of NASH. Mechanistically, we found that Gastrodin protected against NASH by activating the adenosine monophosphate–activated protein kinase (AMPK) pathway, which was supported by the result that the AMPK inhibitor Compound C or AMPK knockdown blocked the Gastrodin‐mediated hepatoprotective effect. Conclusions: Gastrodin attenuates steatohepatitis by activating the AMPK pathway and represents a therapeutic for the treatment of NASH.